210Pb and 137Cs in margin sediments of the Arctic Ocean: Controls on boundary scavenging. Issue 2 (15th May 2013) - Kuzyk, Zou Zou A.; Gobeil, Charles; Macdonald, Robie W.
Abstract: [1] 210 Pb and 137 Cs were measured in 25 sediment cores collected during the International Polar Year from a transect spanning the North American Arctic margin, from the North Bering Sea to Baffin Bay/Davis Strait. Profiles and inventories of the radioisotopes were used to determine sediment mixing and accumulation at each site and to assess the intensity of scavenging and burial. Sediment accumulation rates derived from 210 Pb and validated using 137 Cs are between ≤0.04 and 0.23 g cm −2 yr −1 . 210 Pb cannot be used to derive sedimentation rates for vigorously biomixed sediments from the North Bering‐Chukchi shelf. Elevated 137 Cs activities and inventories in recently deposited sediments imply delayed inputs of particle‐associated 137 Cs to the sediments, likely transported from the watershed to the coast and subsequently redistributed to shelf/slope sediments. Inventories of 210 Pbex in all cores meet or exceed the estimated supply of 210 Pbex from atmospheric deposition and decay of 226 Ra in the water column. This implies that in contrast to the deep Arctic Ocean basin, there is a sufficient supply of suspended particulates along the North American Arctic margin to scavenge the supply of 210 Pbex . 210 Pbex inventories in sediments are up to 21‐fold greater than the in situ supply at some sites. Large inventories of 210 Pbex in sediments along the North Bering‐Chukchi shelf result primarily from focusing, while those along the north Chukchi slope (Barrow Canyon) and in Baffin Bay/Davis Strait reflect strong boundary scavenging, likely supported by lateral exchanges with deep/interior Atlantic‐origin waters. Key Points: 210Pb and 137Cs analyzed in sediment cores from North Bering Sea to Davis Strait Efficient scavenging of 210Pb all along margin relative to interior Arctic Ocean Strong boundary scavenging in north Chukchi slope and Baffin Bay/Davis Strait